2013
DOI: 10.1136/annrheumdis-2013-eular.507
|View full text |Cite
|
Sign up to set email alerts
|

OP0302 Moderate to High Disease Activity in Psoriatic Arthritis is Associated with Elevated Total Cholesterol and Triglycerides

Abstract: Background Psoriatic arthritis (PsA) is associated with a higher frequency of abnormal lipids and obesity compared with healthy controls and rheumatoid arthritis. There is also an increased risk of developing PsA in obese individuals, perhaps related to the inflammatory milieu provided by excess adiposity. It is also known that inflammatory cytokines contribute to derangements in lipid metabolism. However, the relationship between disease activity and lipid profiles in PsA is not well studied. Objectives To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent data suggest that these abnormalities correlate with disease activity and severity. Labitigan et al 39 reported that high disease activity in PsA is associated with an atherogenic lipid profile in the CORRONA database. We have shown that the metabolic syndrome and related adipokines correlate with disease activity in PsA 40.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that these abnormalities correlate with disease activity and severity. Labitigan et al 39 reported that high disease activity in PsA is associated with an atherogenic lipid profile in the CORRONA database. We have shown that the metabolic syndrome and related adipokines correlate with disease activity in PsA 40.…”
Section: Discussionmentioning
confidence: 99%